Evaluation of the effect of injectionsof both platelet-rich plasma and hyaluronic acid in patients with early knee osteoarthritis via the concentration of interleukin-1β in serum - Albdeery, Ali; Alzamily, Ajil (Journal of Biomedicine and Biochemistry, 2022)
Background Early knee osteoarthritis, which causes the degeneration of articular cartilage and subchondral bone, is a disease that worsens with time and is a major contributor to physical disability. Several inflammatory cy- tokines released by chondrocytes work in concert to trigger the production of enzymes that break down cartilage. A pro-inflammatory cytokine called interleukin-1β (IL-1 β ) accelerates cartilage breakdown after trauma, re- duces matrix production, and results in chondrocyte death. Dendritic cells and macrophages are the main sources of IL-1β. On the other hand, os- teoblasts, periodontal ligament cells, and gingival fibroblasts have the abil- ity to release IL-1β. Treatment pure- platelet rich plasma (P-PRP) effec- tiveness of transforming growth factor, platelet-derived growth factor, type I insulin-like growth factor, and the vascular endothelial growth factor is thought to be related to their release. Because of their capacity to increase matrix formation, growth factors have been widely researched for OA and cartilage regeneration. Hyaluronic acid (HA) is a glycosaminoglycan poly- mer composed of N-acetyl glucosamine and D-glucuronic acid disaccharide molecules. Early embryonic development, inflammatory, wound repair, cell differentiation, and viscoelasticity are all affected by HA, and other biologi- cal processes. Materials and Methods Elabscience kits were used to assess the serum IL-1β level. The experimental investigation included 18 control groups, 10 HA injections, and 21 pure PRP injections. age ranged from 30 to 80. The study was excluded all individuals with advanced osteoarthritis in the knee, COVID-19, diabetes, and autoimmune diseases. the time frame running from November 2021 until June 2022. Other variables in our research were age, gender, family history, use of antihypertensive medications or medica- tions for other disorders, and body mass index (BMI). Results The findings of this study demonstrate elevated IL-1β levels in patients with early KOA before treatments injection compared with the healthy control. After treatments injection, the level of IL-1β was decreased compared with before injection. Conclusions IL-1β could be one of the prognostic signs of early KOA